Our minds, our selves a brief history of psychology - Oatley, Keith (Princeton University Press, 2018)
This book provides an original history of psychology told through the stories of its most important breakthroughs and the people who made them. It discusses forms of conscious and unconscious knowledge; brain physiology; emotion; stages of mental development; language; memory; mental illness; morality; free will; creativity; the mind at work in art and literature; and our ability to cooperate with one another. It includes controversial experiments and biographical sketches--Publisher's website.